PKM TANGRAM UNTUK SISWA KELAS VI MIN I KOTA PADANG - Refnywidialistuti; Yuliani Fitri (LPPM Universitas Ekasakti, 2024)
The background to this service is due to the students' lack of understanding of mathematical concepts at MIN 1 Padang City, especially regarding geometry in flat shapes. This activity aims to help students easily understand the concept of flat shapes. Geometry material is conveyed through tangram games. From a square piece of paper, students are asked to cut it into 7 flat shapes consisting of 2 large triangles, 1 medium sized triangle, 2 small triangles and 1 square, and 1 parallelogram. After students are able to do it, then students are asked to measure it and calculate the area of the flat shape. By providing this counseling, it can be seen that students appear enthusiastic and enthusiastic in learning mathematics and are able to complete the tangram game well. This is in accordance with the results of research conducted by several people who focused on discussing tangram.